Single-port laparoscopic ovarian cystectomy of teratoma during pregnancy - Hsiao-Wen Tsai; Chih-Yao Chen; Peng-Hui Wang; Ming-Jie Yang; Nae-Fang Twu; Ming-Shyen Yen; Kuan-Chong Chao; Yi-Jen Chen (Wolters Kluwer Medknow Publications, 2013)
A 31-year-old pregnant woman complained of occasional abdominal pain with a gradually enlarging ovarian cyst at 14 weeks of gestation. Follow-up sonography confirmed the right ovarian cyst, 8.5 cm in size, with regional diffuse bright echoes and hyperechoic lines and dots. Mature cystic teratoma was diagnosed. Single-port laparoscopic surgery was scheduled to prevent cyst enlargement or torsion during pregnancy. Enucleation of the cyst was conducted smoothly without intra-abdominal spilling and removed through the transumbilical port. The overall blood loss was 50 mL. The operative time was 2 hours, and there were no intraoperative complications. Histology of the cyst confirmed a mature cystic teratoma. There was no preterm labor during follow-up. We successfully performed single-port laparoscopic ovarian cystectomy during pregnancy, which was followed by an unremarkable antenatal course. The benefit and safety of single-port laparoscopic cystectomy make it a good alternative choice for surgical intervention during pregnancy.